Correction: Corrigendum: Notch signal strength controls cell fate in the haemogenic endothelium - Leonor Gama-Norton (Nature Portfolio, 2016)
Nature Communications 6: Article number: 8510 (2015); Published: 14 October 2015; Updated: 4 March 2016 The original version of this Article contained a typographical error in the spelling of the author Zhenyi Liu, which was incorrectly given as Zenhy Liu. This has now been corrected in both the PDFand HTML versions of the Article.